PEMIKIRAN ABDURRAHMAN WAHID TENTANG MULTIKULTURALISME DALAM PENDIDIKAN AGAMA ISLAM - M Syaifudin, M Syaifudin; Imam Syafi'i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abdurrahman Wahid's (Gus Dur) thoughts on multiculturalism in Islamic religious education emphasize the importance of the values ​​of inclusivism, pluralism, humanism, and democracy as a basis for responding to the diversity of Indonesian society. This article discusses how Gus Dur's ideas can be implemented in Islamic religious education through a contextual curriculum, strengthening tolerance-based character education, and the active role of teachers and educational institutions in forming moderate and open attitudes in students. This study also highlights a case study of an inclusive Islamic boarding school that applies multicultural principles in real terms and its impact on students' social behavior. This study uses a descriptive qualitative method with a literature study approach, through an analysis of Gus Dur's works and related educational references. The results of the study show that Gus Dur's thoughts are very relevant to be used as a foundation for developing Islamic religious education that is more adaptive, peaceful, and in line with national and humanitarian values.